Optimasi Kondisi Proses Sintesis Biodiesel Berbasis Reaksi Esterifikasi Palm Fatty Acid Distillate Dengan Katalis Cu-Hidroksiapatit Dari Limbah Tulang Ikan - Muhammad Rahman; Yelmida Aziz; Panca Setia Utama (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2021)
Biodiesel is an alternative fuel to a diesel engine that can replace or reduce the use of petroleum diesel. PFAD (Palm Fatty Acid Distillate) is a by-product of physical refining of crude palm oil products and is contained of free fatty acid (FFA) more than 85 wt.%. Esterification is a chemical reaction used to produce biodiesel from feedstocks with high FFA. Hydroxyapatite derived from waste fish bones has been effectively utilized as a support for preparation of the heterogeneous copper acid catalyst. The Copper- Hydroxyapatite catalyst has been prepared through wet-impregnation.This study intends to produce biodiesel with Cu- Hydroxyapatite catalyst derived from fishbone waste in esterification of PFAD and methanol. Esterification reaction parameters were varied to obtain the maximum yield of biodiesel. Optimization of esterification reaction parameters such as methanol to PFAD ratio, catalyst loading, and reaction temperature was carried out by Response Surface Methodology-Central Composite Design (RSM-CCD). The optimum yield obtained using regression models were found to be reaction temperature 62oC, catalyst to PFAD weight 1,82 wt.%, and PFAD to methanol molar ratio 1:8,28. The reaction under the optimum condition predicted at 92,52% of biodiesel yield.